Particle loading method commonly used for preparing photocathode by particle transfer method and application

By using the particle loading method in the particle transfer method, the particles are evenly spread out on the liquid interface, solving the difficulty of uniform particle transfer and control and other technical problems, achieving high-quality photoelectrode preparation and improving photoelectrochemical performance.

CN119680852AInactive Publication Date: 2025-03-25ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510200805.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When preparing the photoelectrode, the particle transfer method has problems such as difficulty in uniform transfer and control of particles, poor contact between particles and substrates, difficulties in achieving ohmic contact, damage and morphological changes in particle transfer, complexity of substrate surface treatment, and insufficient process repeatability and scalability.

Method used

Using a particle loading method, by dispersing the particles to be loaded in a first solvent, after sonication, it is sprayed onto the formed liquid interface, and the interaction between the first solvent and the liquid interface is used to drive the particles to spread uniformly on the interface to form a dense particle film, and the substrate is slowly lifted to achieve uniform transfer of particles.

Benefits of technology

This method effectively improves the film flatness, reduces the resistance between particles, enhances the ohmic contact between particles and the substrate, thereby improving photoelectrochemical performance, and is suitable for large-area electrode preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680852A_ABST
    Figure CN119680852A_ABST
Patent Text Reader

Abstract

The invention discloses a general particle loading method for preparing a photocathode by a particle transfer method and application, and the method comprises the following steps: dispersing particle powder to be loaded in a first solvent, and carrying out ultrasonic treatment to obtain a particle suspension; spraying the particles to a liquid interface formed by treating a second solvent, and driving the particles to uniformly spread on the liquid interface only through the interaction of the first solvent and the liquid interface to form a compact particle film; and inserting the substrate into a liquid interface, slowly lifting and gradually flattening the angle between the substrate and the liquid level, thereby completing the transfer of the particles. According to the method disclosed by the invention, the characteristics of a dispersion solvent-liquid interface are ingeniously utilized, self-confinement spreading and compact arrangement of particles are realized, the method is a more efficient and controllable particle transfer technology, and an extremely thin particle film with higher quality can be prepared, so that the photoelectrocatalysis performance of the photocathode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectric catalytic material preparation, and relates to a particle loading method and application generally used for preparing a photocathode by a particle transfer method. Background Art

[0002] The particle transfer method is an advanced technology for preparing particle-type photoelectrodes. It is mainly used to effectively transfer semiconductor particles to a conductive substrate to form a high-performance photoelectrode. Its core method is to control the deposition method of the particles so that the surface of the photoelectrode is loaded with thinner (ideally a single layer) semiconductor particles as much as possible. This structure can significantly improve the light absorption capacity and charge transfer efficiency of the photoelectrode, and avoid the high resistance and low light absorption problems caused by the accumulation of multi-layer particles. In addition, the particle transfer method can select a metal substrate that forms a good ohmic contact with the particle material, thereby further promoting the transmission of carriers between the particles and the metal substrate. Compared with conventional coating methods (such as drop coating, spin coating, and pulling methods) and other electrode preparation methods (such as electrodeposition, electrophoretic deposition, vacuum deposition, etc.), the particle transfer method has significant advantages: it can achieve the preparation of electrodes with uniform particle coverage without being limited by the material synthesis temperature and the heat resistance of the conductive substrate. At the same time, by regulating the work function of the metal contact layer, an ohmic contact is formed, thereby significantly improving the transmission efficiency of photogenerated carriers to the conductive substrate and improving the performance of the photoelectrode. In addition, the particle transfer method retains the high crystallinity and morphological integrity of the particles while having a good conductive contact layer and excellent mechanical strength, which is suitable for the preparation of high-efficiency photocathode materials, providing new ideas for photoelectrocatalytic water splitting, solar cells and other photoelectric conversion applications. However, this method often has the following technical difficulties and shortcomings in the preparation of photoelectrode applications: 1. Difficulty in uniform particle transfer and control The core of the particle transfer method is to accurately transfer semiconductor particles to a conductive substrate to form a structure that is as thin as possible and evenly covered. However, the following issues may affect the realization of this process: 1) Particle size and morphology control: When achieving near monolayer particle coverage, the size and morphology of the particles are critical to uniformity. Particles with uneven sizes or complex morphologies are prone to stacking or agglomeration during the transfer process, resulting in uneven surface distribution and affecting the performance of the photoelectrode.

[0003] 2) Uniformity of particle deposition: Although the particle transfer method aims to achieve uniform coverage of particles close to a single layer, in actual operation, due to the interaction between particles (such as van der Waals forces, electrostatic effects) and the difference in substrate surface energy, it may lead to uneven distribution of particles, forming local particle accumulation or gaps, reducing the light absorption capacity and charge transfer efficiency of the electrode.

[0004] 3) Poor contact between particles and substrate: During the particle deposition process, it is critical that the particles form good contact with the conductive substrate. However, due to the rough surface or irregular morphology of the particles, there may be incomplete contact or partial suspension between the particles and the substrate, resulting in reduced charge transfer efficiency.

[0005] 2. Difficulties in achieving ohmic contact between particles and substrate An important advantage of the particle transfer method is the ability to select a suitable metal substrate to form a good ohmic contact to facilitate carrier transport. However, there are still some difficulties in achieving an ideal ohmic contact in actual operation: 1) Work function matching problem of metal substrate: Although in theory it is possible to form an ohmic contact by selecting a suitable metal substrate to match the work function of semiconductor particles, in practical applications, work function matching is not always easy to achieve. The surface state and defects of semiconductor materials will affect their actual work function, resulting in the formation of a Schottky barrier between the semiconductor material and the metal substrate, which inhibits charge transfer.

[0006] 2) Charge recombination caused by interface states: Interface states may exist at the interface between particles and conductive substrates. These interface states can capture photogenerated electrons or holes, induce charge recombination, and significantly reduce photoelectric performance. How to effectively inhibit the formation of interface states and eliminate interface recombination is one of the technical challenges faced by the particle transfer method.

[0007] 3. Damage and morphological changes during particle transfer The particle transfer method requires the pre-synthesized high-quality semiconductor particles to be transferred to the substrate by drop coating, LB film technology, etc. This process may damage the performance of the particles themselves: 1) Damage to particle morphology: During the transfer process, the particles may be subjected to mechanical stress, resulting in changes in morphology, especially for some brittle materials, the particles may break or deform during the transfer process. This damage will weaken the particles' light absorption ability and charge transfer performance.

[0008] 2) Introduction of particle surface defects: During the transfer process, mechanical scratches or local defects may occur on the particle surface, which will become charge recombination centers and reduce the overall efficiency of the photoelectrode.

[0009] 4. Complexity of substrate surface treatment To ensure that particles can be transferred evenly and form good contact with the substrate, the surface treatment of the substrate is crucial. However, the substrate surface treatment process may bring some additional technical challenges: 1) Surface cleanliness and roughness control: The cleanliness and roughness of the substrate surface will directly affect the particle deposition effect. A surface that is too smooth may cause the particles to be deposited loosely and easily fall off; while a surface that is too rough may cause uneven particle distribution and affect the performance of the photoelectrode.

[0010] 2) Chemical stability of surface modification: In order to enhance the bonding between particles and substrates, the substrate surface may need to be chemically modified. However, some modified layers may decompose or fail in long-term use, especially in corrosive environments such as electrolytes, resulting in gradual detachment of particles or electrode failure.

[0011] 5. Process repeatability and scalability The particle transfer method may show good results in the laboratory, but in large-scale production, the repeatability and scalability of the process is an important consideration, that is, the controllability is poor: the particle transfer method has high requirements on the particle size, morphology, surface functionalization and other aspects of the material, and the control of these factors may be difficult to accurately adjust in large-scale production, resulting in inconsistent performance between batches. Based on this, the present invention provides a simpler and more feasible coating solution, which improves the flatness of the coating, thereby optimizing the particle uniformity of the electrode and enhancing its photoelectrochemical performance. Summary of the invention

[0012] The purpose of the present invention is to address the deficiencies of the prior art and provide a particle loading method and application generally applicable to preparing photocathodes by a particle transfer method.

[0013] The technical solution adopted by the present invention is as follows: A particle loading method generally used for preparing a photocathode by a particle transfer method comprises the following steps: Dispersing the particle powder to be loaded in the first solvent and ultrasonicating to obtain a particle suspension; Taking a second solvent for treatment to form a liquid interface; Spraying the particle suspension onto the liquid interface, driving the particles to spread evenly on the liquid interface only through the interaction between the first solvent and the liquid interface, to form a dense particle film; A clean substrate is vertically inserted into the liquid interface where the particle film is located, and then the substrate is slowly lifted and its angle with the liquid surface is gradually flattened. During the process, the particle film is evenly attached to the surface of the substrate to complete the transfer of the particles.

[0014] In the above technical solution, further, the first solvent is isopropanol; Furthermore, the second solvent is distilled water or deionized water; Furthermore, the treatment to form a liquid interface specifically includes placing distilled water or deionized water in a container and cooling it to a low temperature state to form a fully liquid ice-water interface; Furthermore, the low temperature state is below 5°C but above 0°C.

[0015] Furthermore, the spraying is to add the particle suspension into an atomizer and spray through the atomizer.

[0016] The present invention also provides a particle film, which is prepared by the particle loading method as described above; Furthermore, the particle film is LaFeO 3 Granular film, copper gallium oxide CuGaO 2 Granular film, copper iron oxide CuFeO 4 Granular film or tin niobate SnNb 2 O 6 Particle film; its thickness is usually less than 5μm.

[0017] The present invention also provides a photocathode, which is prepared based on the particle film as described above.

[0018] The beneficial effects of the present invention are: The present invention selects a first solvent to disperse particles, and treats a second solvent to form a liquid interface, and utilizes the interfacial tension difference between the two to drive the particles to spontaneously spread into a thin film on the liquid interface, thereby forming a dense and uniform thin film. At the same time, the rapid volatilization of the first solvent is utilized to further help the particles to be stably deposited on the interface, thereby avoiding the accumulation and uneven distribution of particles. In addition, since the present invention is driven by interfacial tension difference, even if the particles have limited dispersibility in the suspension, the driving effect of the interfacial tension difference can further promote the spreading and uniform arrangement of the particles on the liquid surface, which effectively reduces the dependence of the method on the dispersibility and size of the particles. The spreading method is combined with the method of lifting the substrate to scoop up the particle film, which effectively avoids mechanical extrusion or excessive collision accumulation between particles, avoids the damage of particles to the particles during the coating process by traditional technology, further protects the morphological integrity of the particles, and is conducive to retaining their high crystallinity; it can be seen that the use of this method can effectively improve the flatness of the film, significantly reduce the resistance between particles, and enhance the ohmic contact between particles and the substrate, thereby improving the photoelectrochemical performance, and the method can be particularly used to prepare large-area electrodes.

[0019] Compared with traditional particle transfer methods such as drop coating and LB film technology, the method of the present invention has outstanding advantages, specifically: Compared with LB film technology, LB film technology is more inclined to "top-down" forced arrangement. They usually need to use external forces (such as compression barriers) to force the particles to be arranged together, that is, they need to increase pressure from the outside to make the molecules arrange closely; this method is easy to form multi-layer stacking and easy to introduce defects. The method of the present invention is a "bottom-up" self-assembly process, which uses the high surface tension difference between the dispersed solvent and the liquid interface to allow the particles to "spontaneously" find the lowest energy arrangement. This self-assembly process is more natural, forming a thinner and more stable structure with fewer defects. Moreover, LB film technology is often expensive in equipment, complicated in operation, low in efficiency, and difficult to apply on a large scale. The method of the present invention is simple in equipment, easy to operate, low in cost, easy to scale up for production, and has obvious efficiency and cost advantages.

[0020] Compared with the drop coating method, the method of the present invention has significant advantages in terms of uniformity, density, thickness control, requirements for particle dispersion, substrate adaptability, etc. of the obtained film: 1. Film uniformity: The drop coating method is to directly drop the particle suspension onto the substrate, and then rely on the solvent to evaporate to form a film. The biggest problem with this method is that it is difficult to control the uniformity of the film. Since the solvent is affected by various factors such as surface tension, gravity, and substrate surface properties during the volatilization process, the "coffee ring" effect is likely to occur, that is, the solute is enriched at the edge of the droplet, resulting in a thick edge and a thin center of the film, and even holes and cracks. In addition, the drop coating method has high requirements for the concentration and dispersibility of the particles. If the particles are not evenly dispersed, it is easy to form agglomerates in the film. The method of the present invention is to spray the particle suspension evenly to the liquid interface, especially by using an atomizer, to avoid the problem of local excessive concentration of the droplets in the drop coating method, and ensure the uniform distribution of the particles from the source. The rapid spreading and self-limiting effect of the dispersed solvent at the liquid interface enable the particles to be evenly dispersed on a two-dimensional plane, forming a structure closer to a single layer, effectively avoiding the "coffee ring" effect and particle agglomeration. At the same time, the process of slowly pulling the substrate from the liquid interface can evenly transfer the particle film to the substrate, maintaining the integrity and uniformity of the film.

[0021] 2. Film density: The film formed by the drop coating method is usually loose, with large gaps between particles. This is mainly because the particles lack effective driving force to arrange closely during the solvent volatilization process. In the method of the present invention, the high surface tension difference between the dispersed solvent and the liquid interface not only drives the spreading of isopropyl alcohol, but also exerts lateral pressure on the particles, prompting the particles to be closely arranged to form a dense thin layer structure. This close arrangement can minimize the gaps between particles and improve the density of the film.

[0022] 3. Film thickness control: The control of film thickness by the drop coating method mainly relies on adjusting the concentration of the particle suspension and the volume of the drop coating, but this control method has low accuracy and it is difficult to achieve accurate film preparation. The method of the present invention can achieve the preparation of thinner particle films through the self-limiting spreading mechanism of the dispersed solvent at the liquid interface, and the control of film thickness is more accurate. It is possible to consider regulating the thickness of the film to a certain extent by adjusting the number and concentration of spraying, but its core advantage is that it can prepare relatively thinner, high-quality, uniform films.

[0023] 4. Requirements for particle dispersibility: The drop coating method has very high requirements for the dispersibility of particles in the solvent. If the particles are not evenly dispersed, it is easy to form agglomerates in the film, affecting the quality and performance of the film. Although the method in the present invention also requires the particles to have good dispersibility in the first solvent, the requirement for particle dispersibility is relatively low due to the use of a spray coating method. Even if there is a small amount of particle agglomeration, the agglomerates are more easily broken up during the spraying and spreading process.

[0024] 5. Substrate adaptability: The drop coating method is sensitive to the surface properties of the substrate, such as the wettability and roughness of the substrate, which will affect the quality of the film. In comparison, the method of the present invention is less dependent on the substrate because the spreading and arrangement of particles mainly occur at the liquid interface rather than the substrate surface. As long as the substrate has a certain degree of hydrophilicity and can form good contact with water, effective transfer of the film can be achieved.

[0025] The method of the present invention cleverly utilizes the characteristics of the dispersed solvent-liquid interface to achieve self-limited spreading and close arrangement of particles. It is a more efficient and controllable particle transfer technology that can produce higher quality and smaller particle films, thereby improving the photoelectrocatalytic performance of the photocathode. This method is a major upgrade of the traditional drop coating method and provides a new idea and method for preparing high-performance photoelectrocatalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The spraying effect at the ice-water interface when isopropyl alcohol is used as the first solvent; Figure 2 The spraying effect at the ice-water interface when acetone is used as the first solvent; Figure 3 The spraying effect at the ice-water interface when n-propanol is used as the first solvent; Figure 4 The spraying effect at the ice-water interface when ethanol is used as the first solvent; Figure 5a , Figure 5b , Figure 5c , Figure 5d The SEM images of the particle morphology after the traditional drop coating method and the transfer method of the present invention at different magnifications are shown in FIG. Figure 5a-5d The left picture in the middle shows the traditional drop coating method, and the right picture shows the method of the present invention; Figure 6 The chronoamperometry (CA) of the photocathode obtained by the conventional drop coating method and the transfer method of the present invention is shown; Figure 7 The cyclic voltammogram (CV) of the photocathode obtained by the conventional drop coating method and the transfer method of the present invention; Figure 8 These are photos of the films obtained in Examples 1, 5 to 7; Fig. 9 The surface SEM images of the film obtained in Example 5, wherein the left image is a low-magnification SEM image, and the right image is a high-magnification SEM image; Fig.10 The surface SEM images of the film obtained in Example 6, wherein the left image is a low-magnification SEM image, and the right image is a high-magnification SEM image; Fig.11 is a cross-sectional SEM image of the film obtained in Example 6; Fig.12 The surface SEM images of the film obtained in Example 7, wherein the left image is a low-magnification SEM image, and the right image is a high-magnification SEM image; Fig.13 is a cross-sectional SEM image of the film obtained in Example 1; Fig.14 is a cross-sectional SEM image of the film obtained in Comparative Example 1; Fig.15 This is the laser confocal result of the photocathode finally obtained in Example 1; Fig.16 This is the laser confocal result of the photocathode finally obtained in Comparative Example 1; Fig.17 The CV performance comparison between the photocathode finally obtained in Example 5 and the photocathode obtained by the conventional drop coating method; Fig.18 The CV performance comparison between the photocathode finally obtained in Example 6 and the photocathode obtained by the conventional drop coating method; Fig.19 The CV performance comparison between the photocathode finally obtained in Example 7 and the photocathode obtained by the traditional drop coating method is shown in FIG. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0028] 1. Implementation Cases: Example 1

[0029] Lanthanum ferrite LaFeO 3 Taking the preparation of a photoelectrode as an example, based on the method of the present invention, the preparation process includes: (1) Using the solid phase molten salt method to 2 O 3 :LaO:Na 2 SO 4 =1:1:5 ratio in a tube furnace at 1000 °C for 10 h, and then washed several times and dried in an oven at 65 °C for 6 h to obtain pure LaFeO 3 powder; (2) 0.3 g LaFeO 3 The powder was dissolved in 10 mL of isopropanol and ultrasonically dispersed for 30 min to obtain a uniformly dispersed LaFeO 3 Isopropyl alcohol suspension; (3) Make a small spray vibration atomization component. It uses the humidification drive circuit board module as the power switch, and then use a USB humidifier special microporous atomization sheet and a plastic tube with a diameter of 1 cm and a height of 2 cm to bond with the silicone rubber special adhesive K-907 to make a small atomizer, which is connected to the humidification drive circuit board module and is subsequently called the atomizer; use a 200mL beaker to receive distilled water (i.e. ice water) taken out of the refrigerator (4°C) as a carrier for subsequent steps; (4) Disperse the uniformly dispersed LaFeO 3 The isopropanol suspension was sucked up with a rubber-tipped dropper and slowly dripped into the homemade atomizer. At the same time, the atomizer switch was turned on to make LaFeO 3 The isopropanol suspension was sprayed in a mist form and sprinkled on distilled water, driving the LaFeO 3 The particles spread evenly on the ice-water interface to form a dense and flat particle film; (5) A 1 cm*3 cm frosted glass piece that had been cleaned with distilled water ultrasonically for 30 mins was inserted into the formed LaFeO 3 In the film, the frosted glass is 90° to the liquid surface. Then the frosted glass is gently lifted by hand (the angle between the frosted glass and the liquid surface slowly changes from 90° to 180°), and a layer of LaFeO is obtained on the frosted glass. 3 Thin films for subsequent particle transfer method to prepare LaFeO 3 The subsequent particle transfer method of the photocathode usually involves evaporating a conductive layer on the thin film layer, which in the example of the present invention is 5μm thick tin and 0.35μm nickel, and then using single-sided tape (the thickness of the single-sided tape used in the experiment is about 13μm) to peel off the conductive layer and the thin film layer from the frosted glass to obtain the photocathode film. However, in order to better fix it for application, the single-sided tape side of the photocathode film is fixed to the glass substrate by double-sided tape (the thickness of the double-sided tape used in the experiment is about 37μm) to ensure the mechanical stability of the electrode.

[0030] Example 2

[0031] The same as Example 1, except that the isopropyl alcohol in (2) is replaced by acetone.

[0032] Example 3

[0033] The same as Example 1, except that the isopropanol in (2) is replaced by n-propanol.

[0034] Example 4

[0035] The same as Example 1, except that the isopropanol in (2) is replaced by ethanol.

[0036] Example 5

[0037] Copper Gallium Oxide CuGaO 2 Preparation of photoelectrode: The method of steps (2) to (5) in Example 1 is adopted, except that LaFeO 3 Powder replaced with CuGaO 2 powder.

[0038] Example 6

[0039] Copper iron oxide CuFeO 4 Preparation of photoelectrode: The method of steps (2) to (5) in Example 1 is adopted, except that LaFeO 3 Powder replaced with copper iron oxide CuFeO 4 powder.

[0040] Example 7

[0041] SnNb 2 O 6 Preparation of photoelectrode: The method of steps (2) to (5) in Example 1 is adopted, except that LaFeO 3 Powder replaced with tin niobate SnNb 2 O 6 powder.

[0042] Comparative Example 1 The LaFeO prepared in Example 1 is used 3 The isopropanol suspension was transferred to a cleaned frosted glass surface with a size of 1 cm*3 cm by conventional drop coating method and used for the subsequent preparation of LaFeO 3 Photocathode.

[0043] 2. Performance Analysis: Figure 1-Figure 4 The particle spreading diagrams at the liquid interface after spraying corresponding to Examples 1 to 4 are shown. 3Other particles except for acetone were also subjected to corresponding experiments, and they all showed similar trends. From the state of the suspension and the effect of spraying, the use of isopropanol as the first solvent is better than acetone, n-propanol, and ethanol in terms of the stability of the suspension and the uniformity of the film in the state of particle spreading after spraying. The analysis is as follows: For the first solvent in the scheme of the present invention, i.e., the dispersion solvent, its evaporation rate, miscibility with water, wettability, and viscosity have an important influence on the spreading effect of the sprayed particles. Too fast evaporation rate is prone to cause the "coffee ring" effect and uneven film formation. During the spraying process, the dispersion solvent will evaporate rapidly, especially at the edge of the droplet. This uneven volatilization will cause the solvent to flow from the center of the droplet to the edge to supplement the solvent volatilized at the edge. This flow will carry the particles to migrate to the edge together, eventually causing the particles to accumulate at the edge, forming a "coffee ring" effect, while the particles in the central area are sparse and cannot form a uniform and dense film. The formed film has thick edges and thin centers, and even the central area may not be covered by particles at all. In addition, rapid volatilization will also cause the solvent environment around the particles to change rapidly, and the interaction forces between the particles (such as van der Waals forces) will increase rapidly, causing the particles to aggregate and agglomerate before they can be evenly dispersed on the interface. A large number of particle agglomerates are likely to exist in the formed film, which will reduce the photoelectric conversion efficiency of the film and affect the uniformity and stability of the film. The core of the method of the present invention is to use the large surface tension difference of the ice-water interface to drive the spreading of the particles. Since the second solvent is partially miscible with water to form a stable liquid film at the ice-water interface, it provides a platform for the particles to spread. If it is completely miscible with water, when it is sprayed on the ice-water interface, it will quickly dissolve in water, destroying the original surface tension structure of the ice-water interface, and unable to form a stable liquid film. The particles cannot be spread in an orderly two-dimensional manner on the interface, but may be directly dispersed into the water body, or disorderly aggregated on the interface, and the desired thin layer structure cannot be formed. However, a slower volatilization rate is not conducive to the rapid fixation of particles at the ice-water interface and the stability of the film layer. It may also cause solvent residues in the film, affecting the quality and stability of the film. Viscosity, etc. will also affect the particle dispersion effect.

[0044] It can be seen that isopropanol is selected as the first solvent because it perfectly balances multiple key factors, making its characteristics highly consistent with the requirements of the method of the present invention, thereby enabling the preparation of high-quality thin-layer particle films. These key factors include: moderate surface tension, moderate evaporation rate, excellent particle dispersion ability, good interaction with the ice-water interface, safety, environmental protection and cost, among which: 1. Moderate surface tension ensures uniform spreading of particles and avoids film formation defects: The surface tension of isopropyl alcohol is 21.7mN / m (20°C), showing moderate wettability. This moderate surface tension is the key advantage of isopropyl alcohol. It can ensure that LaFeO 3The particles have good wettability and spreadability on the ice-water interface, and can avoid problems such as unstable or broken liquid films caused by too low surface tension (such as some surfactants). Ensure that the particles are evenly spread on the ice-water interface to form a dense and uniform film, avoiding film defects such as holes, particle stacking or "coffee ring" effect caused by inappropriate surface tension. 2. The moderate evaporation rate perfectly matches the particle spreading and deposition process: the boiling point of isopropanol is 82.4°C, the saturated vapor pressure is 4.4 kPa (20°C), and it has a moderate evaporation rate. This feature is crucial, which enables the evaporation process of isopropanol to be perfectly synchronized with the spreading and deposition process of particles on the ice-water interface. It not only ensures the rapid evaporation of the solvent to fix the particles and form a stable thin layer structure, but also avoids particle aggregation and "coffee ring" effect caused by too fast evaporation (such as acetone), or solvent residue and long film formation time caused by too slow evaporation (such as n-propanol). It achieves rapid fixation of particles and efficient film formation, while ensuring the uniformity and density of the film, avoiding various defects caused by mismatching volatilization rates. 3. Excellent particle dispersion ability is the prerequisite for uniform film formation: isopropyl alcohol has a great influence on the performance of LaFeO 3 The oxide particles show excellent dispersibility. Through simple ultrasonic treatment, the particles can be evenly dispersed in isopropanol and can maintain long-term suspension stability. The particles are not easy to settle or agglomerate. This is the key prerequisite for subsequent uniform spraying and film formation. It ensures that the particles sprayed to the ice-water interface are evenly dispersed, avoiding film defects caused by particle agglomeration, and laying the foundation for the formation of high-quality films. 4. Good interaction with the ice-water interface provides an ideal driving force for spreading: isopropanol is partially miscible with water and can form a large surface tension difference (51.1 mN / m) with the ice-water interface. This property provides an ideal driving force for the uniform spreading of particles on the ice-water interface. The stable liquid film formed by isopropanol at the ice-water interface provides a good spreading platform for the particles. It promotes the orderly spreading of particles at the ice-water interface, which is conducive to the formation of a uniform, dense and thin film.

[0045] In summary, isopropanol, with its moderate surface tension, volatilization rate, excellent particle dispersion ability, good interaction with the ice-water interface, as well as safety, environmental protection and cost advantages, perfectly meets the requirements of the particle transfer method for preparing photocathode particle loading methods. It can achieve uniform spreading and rapid fixation of particles at the ice-water interface, and finally form a high-quality film, thereby obtaining a photocathode with excellent performance. Other solvents, such as acetone, n-propanol and ethanol, although they may have certain advantages in some aspects, cannot compare with isopropanol in overall performance, and it is difficult to achieve the preparation of high-quality near-monolayer particle films required by the present invention.

[0046] Figure 5a , Figure 5b , Figure 5c , Figure 5d The SEM images of the particle films obtained in Comparative Example 1 and Example 1 at different magnifications, wherein the left image is Comparative Example 1, which is obtained by the drop coating method, and the right image is obtained by Example 1. By comparison, it can be seen that the film prepared by the method of the present invention has significantly improved particle distribution uniformity, film density, and particle morphology integrity compared to the traditional drop coating method.

[0047] Figure 6 , Figure 7 The performance diagram of the photocathode finally prepared in Example 1 and Comparative Example 1 shows that: 1) Chronoamperometry (CA): Compared with the conventional drop coating method, the method of the present invention has a more excellent activation behavior and better long-term stability, which is specifically manifested in: Traditional drip coating method: Initial state and activation behavior: The initial current density is close to 0 mA / cm², which is a normal initial state for the photocathode. After 8 hours of testing, the current density increased from the original 0.092 mA / cm² to about 0.137 mA / cm², and the activation was 1.49 times the original, with low activation power.

[0048] Limited performance improvement: Although the samples prepared by the traditional drop coating method show certain photoreduction activity, the extent of performance improvement is still limited.

[0049] The method of the present invention: Fast activation and significant performance improvement: Similarly, the initial current density of the sample in Example 1 was also close to 0 mA / cm². However, after 18 hours of testing, the current density increased from the original 0.1 mA / cm² to the later 0.201 mA / cm², which was activated by 2 times. This significant activation phenomenon indicates that the sample generated a large number of photogenerated electrons under light and effectively participated in the reduction reaction, showing excellent activation behavior and significant improvement in photoreduction performance.

[0050] In terms of long-term stability: the samples obtained by the method of the present invention maintain the photocurrent density without decay during a longer test time, which fully proves that the photocathode prepared by this method has excellent long-term stability, can resist the influence of adverse factors such as photocorrosion and active site deactivation, and the performance decays more slowly.

[0051] The rapid activation, significant performance improvement and excellent long-term stability exhibited by the samples of the present invention indicate that they have greater potential in practical applications such as photoelectrocatalytic water decomposition to produce hydrogen.

[0052] 2) Cyclic voltammogram (CV): Compared with the photocathode obtained by the conventional method, the photocathode obtained by the method of the present invention has better electrochemical activity and charge transfer ability, which is specifically manifested in: In a 0.5M boric acid solution with pH=9, especially at a potential of @0.43V_RHE, the photocurrent density of the sample prepared by the method of the present invention (yellow curve) is significantly higher than that of the sample prepared by the conventional drop coating method (red curve). At a potential of @0.43V_RHE, the photocurrent density of the sample prepared by the method of the present invention is about 0.229 mA / cm², while that of the sample prepared by the conventional drop coating method is only 0.130mA / cm², which is 1.76 times higher, and the sample of the present invention has a larger CV curve area. This fully demonstrates that the sample of the present invention has a stronger ability to separate and transport photogenerated carriers, as well as a higher active site density, and the sample of the present invention exhibits a higher current density in a wider potential range (e.g., 0.4V to 1.2V vs RHE), which means that it can maintain good photocatalytic activity under a wider range of conditions.

[0053] Figure 8 These are photos of the films obtained in Examples 1, 5 to 7; Fig. 9 This is the surface SEM image of the film obtained in Example 5. Fig.10 , Fig.11 The surface and cross-sectional SEM images of the film obtained in Example 6 are as follows: Fig.12 The SEM image of the film surface obtained in Example 7 shows that the particle films obtained by the method of the present invention are relatively uniform and dense, and the particles are in close contact with each other without forming obvious gaps. Fig.13 , Fig.14 From the SEM image of the film cross section, it can be seen that the film prepared by the method of the present invention is thinner, less than 5μm, and is a uniform, dense, thin, high-quality film, which has significant advantages over traditional methods (drop coating, LB film technology). In addition, the results of laser confocal imaging of the final photocathode also confirm this point, such as Fig.15 , Fig.16 As shown in the figure, the total thickness of the film on the electrode substrate prepared in Example 1 of the present invention is 60 μm, that is, the thickness of the corresponding lanthanum ferrite film is about 4.6 μm, which is close to the cross-sectional SEM measurement result. A thinner semiconductor particle layer is conducive to the rapid separation and transmission of photogenerated carriers, reducing recombination losses, thereby improving the photoelectric conversion efficiency of the electrode. Figure 17~Figure 19 It can be seen that the photocathode prepared by the method of the present invention has relatively better performance.

[0054] 3. Mechanism Analysis A. Analysis of the thin and dense principle mechanism: There are three key factors for the particle film formation in the present invention: the high surface tension difference of the ice-water interface, the moderate evaporation rate of isopropanol, and the good dispersibility of the particles in isopropanol. These three key factors work together to achieve thin and dense: 1. High surface tension difference at the ice-water interface: not only a driving force, but also a "template" and "sieve" "Template" effect: The huge surface tension difference of 51.1 mN / m is not only the driving force for the spreading of isopropyl alcohol, but more importantly, it forms a "template" at the ice-water interface. This "template" has extremely high surface energy, and it tends to combine with substances with lower surface energy to reduce its own energy. The surface tension of isopropyl alcohol (21.7 mN / m) is lower than that of water, so it will spread on the water surface. As a solid, the surface energy of the particles is usually higher than that of isopropyl alcohol, so they will be "trapped" on this "template" and cannot easily penetrate or sink into the water.

[0055] "Sieve" effect: The high surface tension difference at the ice-water interface also acts as a "sieve". It allows isopropyl alcohol molecules to pass through and spread, but prevents larger particles (usually at the nanometer to micrometer scale) from passing through. This confines the particles between the isopropyl alcohol and ice-water interface, providing spatial restrictions for the formation of thin layer structures.

[0056] 2. Microscopic image of self-limited spreading: It can be imagined that when isopropyl alcohol carrying particles is sprayed onto the ice-water interface, the isopropyl alcohol spreads rapidly to form an extremely thin liquid film. In this liquid film, the particles are "sandwiched" from top to bottom: the ice-water interface with high surface tension is below, and the isopropyl alcohol that evaporates gradually is above. As the isopropyl alcohol evaporates, the thickness of the liquid film continues to decrease, and the distance between the particles is also forced to decrease. Finally, when the distance between the particles is reduced to a certain extent, the repulsive force between the particles (electrostatic repulsion, steric hindrance, etc.) begins to play a dominant role, preventing the particles from getting closer and forming a stable thin layer structure. This process is spontaneous and self-limited.

[0057] B. Moderate evaporation rate of isopropyl alcohol: precise "time controller" 1. "Time window": The moderate volatilization rate of isopropyl alcohol provides a valuable "time window" for the orderly arrangement of particles. This "time window" must be just right: if it is too short, the particles will be fixed before they can arrange themselves in order (such as acetone); if it is too long, the particles will have enough time to migrate and aggregate in a disordered manner (such as n-propyl alcohol).

[0058] 2. Dynamic balance: The volatilization of isopropyl alcohol is actually a dynamic balance process. On the one hand, volatilization causes the thickness of the liquid film to decrease, which promotes the particles to get closer; on the other hand, the repulsive force between particles prevents the particles from getting too close. The moderate volatilization rate of isopropyl alcohol allows this dynamic balance to be maintained for a long enough time, allowing the particles to have sufficient time to adjust their positions and find the lowest energy arrangement, that is, a compact thin layer structure.

[0059] 3. Avoid defects: If the volatilization is too fast, the particles will be quickly "frozen" in the current position, unable to effectively self-assemble, and easily form defects and voids; if the volatilization is too slow, the particles may settle under the action of gravity, or disorderly aggregate under the action of Brownian motion, which will also destroy the integrity of the thin layer structure.

[0060] C. Good dispersion of particles in isopropanol: uniform “initial conditions” 1. Quality of "seeds": Good dispersion of particles in isopropanol is the "initial condition" for forming high-quality films. Ultrasonic treatment allows the particles to be evenly dispersed in isopropanol in a single form, just like "seeds". The quality (dispersion) of these "seeds" directly determines the quality of the final "fruit" (film).

[0061] 2. Avoid "congenital deficiencies": If the particles are severely agglomerated in isopropanol, then even if the subsequent spreading and volatilization processes are well controlled, a perfect thin layer structure cannot be formed, because the agglomerated particles will occupy a larger space and destroy the continuity and density of the thin layer structure.

[0062] It can be seen that the method based on the isopropanol-ice-water interface cleverly utilizes the high surface tension difference of the ice-water interface as a "template" and "sieve", the moderate volatilization rate of isopropanol as a "time controller", and the good dispersion of particles in isopropanol as an "initial condition". The three work synergistically to achieve self-limited spreading and self-assembly of the particles, forming a high-quality, dense film that is approximately a single layer.

[0063] Compared with the existing particle transfer method, the method of the present invention is more efficient, economical, universal, and controllable. It is a more advantageous particle transfer technology. It can not only effectively transfer to form a thin film, but more importantly, it can form a thinner and higher quality uniform and dense film, and surpasses the existing particle transfer technology in many aspects. The method of the present invention has great potential in the preparation of high-performance photocathode materials, and also provides new ideas and technical support for the development of photoelectrocatalytic water decomposition, solar cells and other photoelectric conversion application fields.

[0064] The above-described embodiments are only some of the preferred solutions of the present invention, but they are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A particle loading method generally used for preparing a photocathode by a particle transfer method, characterized in that: These include: Dispersing the particle powder to be loaded in the first solvent and ultrasonicating to obtain a particle suspension; Taking a second solvent for treatment to form a liquid interface; Spraying the particle suspension onto the liquid interface, driving the particles to spread evenly on the liquid interface only through the interaction between the first solvent and the liquid interface, to form a dense particle film; A clean substrate is vertically inserted into the liquid interface where the particle film is located, and then the substrate is slowly lifted and its angle with the liquid surface is gradually flattened. During the process, the particle film is evenly attached to the surface of the substrate to complete the transfer of the particles.

2. The particle loading method for preparing photocathode by particle transfer method according to claim 1, characterized in that: The first solvent is isopropanol.

3. The particle loading method for preparing photocathode by particle transfer method according to claim 1, characterized in that: The second solvent is distilled water or deionized water.

4. The particle loading method for preparing photocathode by particle transfer method according to claim 1, characterized in that: The process of forming a liquid interface specifically includes placing distilled water or deionized water in a container and cooling it to a low temperature state to form a fully liquid ice-water interface.

5. The particle loading method for preparing photocathode by particle transfer method according to claim 1, characterized in that: The low temperature state is below 5°C but above 0°C.

6. The particle loading method for preparing photocathode by particle transfer method according to claim 1, characterized in that: The spraying is to add the particle suspension into an atomizer and spray through the atomizer.

7. A particle film, prepared by the particle loading method according to any one of claims 1 to 6.

8. The particle film according to claim 7, characterized in that The granular film is a LaFeO3 granular film, a CuGaO2 granular film, a CuFeO4 granular film or a SnNb2O6 granular film.

9. The particle film according to claim 7, characterized in that The particle film has a thickness of less than 5 μm.

10. A photocathode, characterized in that: The film is prepared based on the particles as claimed in claim 7.

Citation Information

Patent Citations

  • Method for preparing silicon dioxide colloidal crystal film through gas-liquid interface method

    CN106830700A

  • Method and apparatus for producing large-area monolayer films of solution dispersed nanomaterials

    CN109689329A

  • Ultrathin transparent nano / micron structure self-assembly film and green preparation method thereof

    CN110240117A

  • Oriented gas-liquid interface polymer semiconductor film and construction method and application thereof

    CN113540353A

  • Copper bismuth oxide film and preparation method and application thereof

    CN118007171A